Revision of the spider genus Nyetnops Platnick & Lise (Araneae: Caponiidae) with proposition of the new genus Nopsma, from Central and South America - Sánchez-Ruiz, Alexander; Brescovit, Antonio D.; Bonaldo, Alexandre B. (Zootaxa, 2020)
The singular spider genus Nyetnops Platnick & Lise is revised and three new species are described from Peru (Nyetnops naylienae n. sp.), Bolivia (Nyetnops lachonta n. sp.) and Brazil (Nyetnops buruti n. sp.). An updated diagnosis is proposed for the type species Nyetnops guarani Platnick & Lise and new records from the Brazilian State of São Paulo are presented for this species. The Ecuadorian species Nyetnops juchuy Dupérré is elected as the type species of a new genus herein proposed (Nopsma n. gen.), which also harbors three other new species from Peru (Nopsma enriquei n. sp.), Colombia (Nopsma florencia n. sp.) and Nicaragua (Nopsma armandoi n. sp.).